Study of Conceptual Change in Chemistry for Class XI Science High School Students - Hartarti Uminah; Ijirana Ijirana; Siti Nuryanti (Jurnal Akademika Kimia, 2022)
Varied initial concepts can be an obstacle or support in understanding a new concept. The study of changes in students' chemical concepts was carried out on thermochemical material. This study aimed to examine changes in students' thermochemical concepts in each subject of high, medium, and low ability. Qualitative descriptive research with mixed methods was conducted on SMAN 1 Bumi Raya Morowali, Central Sulawesi students. The study began by giving an initial test to all students of class XI IPA 1 and 2, as many as 60 students, to obtain initial concept data and the basis for grouping subjects on each ability criterion (high, medium, and low). Every two people from each ability group in semi-structured interviews. Thermochemical material is re-taught using a metacognitive skill learning model and given a final test and interview to get concept data after learning to assess conceptual changes. Five concepts become variables in this study: the heat of reaction, enthalpy of reaction in a calorimeter, Hess's law, energy diagrams, and bond energies. The results showed that concept changes occurred in all high, medium, and low ability subjects. Changes in students' conceptions occurred in the concepts of the heat of reaction, reaction enthalpy, calorimeter, Hess's law, energy diagrams, and bond energy. The most significant conceptual change occurred in the subject of medium ability and low ability, namely the concept of bond energy.